2021
DOI: 10.3390/microorganisms9040803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactylate and Bacillus subtilis on Growth Performance, Peripheral Blood Cell Profile, and Gut Microbiota of Nursery Pigs

Abstract: To evaluate the effects of lactylate and Bacillus subtilis on growth performance, complete blood cell count, and microbial changes, 264 weaning pigs were assigned to four treatments (1) control (Con) basal diets that met the nutrient requirement for each phase, (2) 0.2% lactylate (LA), (3) 0.05% Bacillus subtilis strains mixtures (BM), or (4) the combination of LA and BM (LA+BM) added to the control basal diet at their respective inclusion rates in each of the three phases. Dietary lactylate tended to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Common probiotics in the swine industry include Lactobacillus and Bacillus . Lactobacillus plays beneficial roles in gut health, such as regulation of intestinal mucosal immunity, maintenance of gut barrier function, and competition with pathogens for binding sites ( 47 , 48 ). It has been identified by CI methods as one of the most abundant genera in pigs, even at different niches of the gastrointestinal (GI) tract ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Common probiotics in the swine industry include Lactobacillus and Bacillus . Lactobacillus plays beneficial roles in gut health, such as regulation of intestinal mucosal immunity, maintenance of gut barrier function, and competition with pathogens for binding sites ( 47 , 48 ). It has been identified by CI methods as one of the most abundant genera in pigs, even at different niches of the gastrointestinal (GI) tract ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are defined as living microorganisms, which, consist of live cultures of bacillus, lactic acid bacteria (LAB), or yeast [ 11 ] and when applied in adequate amounts, confer health benefits for the host [ 12 ]. Studies have shown that the beneficial effects of probiotics on the host include increasing growth rate [ 13 ], improved digestibility [ 14 ], improved and prevention of diarrhea [ 6 ], modulatory effects on the immune system [ 15 ], and reduced harmful gas emissions [ 16 ], etc., At present, Lactobacillus has become a common probiotic supplementation in livestock feed [ 17 ]. L. plantarum is a facultative hetero-fermentative LAB, which usually ferments carbohydrates through the phosphoketolase pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The promotion of the colonization of the gut by beneficial bacteria has also been ascribed to several Bacillus-based probiotics. For instance, B. subtilis favors the intestinal colonization of some beneficial bacteria, including Lactobacillus, Leucobacter, Bifidobacteria, Megasphaera, Coprococcus and Prevotella (Wang et al, 2019(Wang et al, , 2021Ding H. et al, 2021) in nursery and growing pigs. Likewise, in chickens, an increase in Enterococcus (Ciurescu et al, 2020; subtilis ATCC 6051a in broilers), Lactobacillus spp.…”
Section: Favoring the Colonization Of The Gut By Beneficial Bacteriamentioning
confidence: 99%